ماهية النقود الالكترونية - مسعودي, زكرياء; جقريف, الزهرة (University of Eloued جامعة الوادي, 2018)
جاءت هذه الدراسة للوقوف على ماهية النقود الالكترونية، التي ظهرت نتيجة التطور الحاصل في مجال التكنولوجيا، إذ أنها عبارة عن عملة الكترونية ليس لها كيان مادي محسوس، لا تختلف عن النقود العادية إلا من حيث الوسيلة التي يتم تخزينها عليها، م لهذا النوع من النقود جملة من الخصائص والمزايا تنفرد بها عن النقود الورقية، مما جعلها تحظى بقبول المتعاملين بها، وزيادة سرعة انتشارها، إلا أنه من جهة أخرى فإن استخدامها قد تكتنفه مخاطر قانونية وتقنية، كما أن هذه النقود الالكترونية أنواع ، مهي تختلف باختلاف الزاوية التي ينظر إليها، وبما أن النقود الالكترونية عملة لا كيان لها، فقد أثارت طبيعتها جدل فقهي بين من كيفها على أساس أنها صورة غير مادية للنقود الورقية، مبين من اعتبرها أداة تبادل وليست أداة دفع، ومنهم من قال بأنها أداة ائتمان والرأي الأخير اعتبرها صورة افتراضية ثلاثية الأقطاب.This study came to show electronic money definition, which emerged as a result of the development in the field of technology, it is an electronic currency does not have a tangible physical entity, not different from ordinary money except in terms of the means on which it is stored, The advantages and advantages are unique to the paper money, which made them accepted by the customers, and increase the speed of deployment, but on the other hand, the use of the risk of legal and technical, and this electronic money types, and are different depending on the angle that is seen And electronic money A coin that has no entity, has raised its nature of a jurisprudential dispute between its nature on the basis that it is a non-material image of paper money, and among those who considered it an instrument of exchange and not a tool of payment, and some of them said it is a tool of credit and the last opinion considered a hypothetical three-polar image.
Electronic money definition
مقال
Keywords: النقود الالكترونية، النقود الورقية العادية، النقود الالكترونية المحددة، وحدات إلكترونية، الدفع الالكتروني، الخدمات المصرفية.; electronic money, paper money, electronic money specified, modules electronic electronic payment, banking services.